The Critical Success Factors (CSFs) of Green Practices in Halal Food Supply Chain: A Survey among Malaysia Halal Food Companies (S/O 13768) - Abdullah, Rohani; Sabar, Rohafiz; Mustafar, Mastora (UUM, 2020)
The research conducted was to identify The Critical Success Factors (CSFs) of Green Practices in Halal Supply Chain among Malaysian Halal Food producers. The aim of the study is to identify the Critical Success Factors of green Halal practices that can be adopted by the Halal industry to preserve the sustainable development of their business organization. The research objective is investigating the extent of green practices implementation among Halal Halal food companies and to highlight the critical success factors of green practices. Malaysian government now is moving towards its green Agenda and currently is working on its sustainable development. Agriculture and food sectors are among the highest contributor to environmental problems of the country. Therefore, by instiling green practice in food production may rectify these environmental problems. In addition, by introducing and implementing green practices, Malaysian Halal food will be a step ahead to consistently showing that Halal itself is not only an identity for Muslim consumerism but also as a symbol for ecological good practice. Overall, the findings ofthe study reveal the implementation of green Halal practices among Halal food companies in Malaysia can be ranked as favorable and satisfying. Six factors are found to be critical; Return on Investment (ROD is being practiced at a highest level followed by Natural Resources Conservation- (NRC), Health and Safety practices, Support Supply Chain Partners, Green Processing, Pacakaging and Transportation (GPPT) and Green Purchasing. These critical success factors would be useful for the managers of the Halal food companies to implement green practices. This study provides some implications in terms practical applications that can help practitioners to better understand the issues related to the green practices in Halal food industry. The work is limited to Malaysian Halal food industry, but it can be extended to other industry for future study.